Tragedy in Lyme Bay: a whistleblowing cautionary tale - Lovell, Alan (Henry Stewart Talks, 2020)
This case study looks at the Lyme Bay Canoeing tragedy as an example for whistleblowing which, had it been acted upon, would have saved many lives.